Effects of a fat-rich diet on maximal oxygen uptake and time-to-exhaustion in male triathletes - Hetzler, R. K.; Yuen, K. Q.; Graybill-Yuen, R. M.; Titchenal, C. A.; Ho, K. W. (Medicine & Science in Sports & Exercise, 1998)
Male athletes have been reported to improve VO2max and time to exhaustion after consuming a fat-rich diet. Highly trained male triathletes (N = 5) consumed normal, fat-rich, and carbohydrate rich diets, each for seven days before performing a cycle ergometer test. There were no differences in ratings of perceived exertion between trials. The fat-rich diet did not improve VO2max, time to exhaustion, or substrate utilization over the carbohydrate-rich diet effects. Implication. Fat-rich and carbohydrate-rich diets affect endurance performance similarly in males.